Determination of the temperature dependences of thermoelectric parameters of materials used in generator thermoelectric modules with a rise in temperature difference - Anatychuk, L.I.; Lysko, V.V. (Journal of Thermoelectricity, 2021)
A method is proposed for determining the thermoelectric parameters of materials used in generator thermoelectric modules in the case when the cold side of module is thermostated, and the temperature difference across the module gradually increases due to a rise in the hot side temperature with the help of an electric heater. A detailed physical model of this method is considered and the results of estimating possible values of measurement errors are presented.